(untitled) - Siriwongpairat, W. Pam (Hoboken, N.J., 2007)
Ultra-Wideband Communications Systems is the first book to provide comprehensive coverage of the fundamental and advanced issues related to UWB technology, with a particular focus on multiband orthogonal frequency division multiplexing (multiband OFDM). The multiband OFDM approach was a leading method in the IEEE 802.15.3astandard and has recently been standardized by ECMA International. The book also explores several major advanced state-of-the-art technologies to enhance the performance of the standardized multiband OFDM approach.
Keywords: Orthogonal frequency division multiplexing,Ultra-wideband devices,Phân chia tần số phát sóng,Thiết bị băng thông rộng